2016
DOI: 10.5114/fmpcr/59301
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the patients’ with minor injuries attendance to the Emergency Department

Abstract: A -przygotowanie projektu badania, B -zbieranie danych, C -analiza statystyczna, D -interpretacja danych, E -przygotowanie maszynopisu, F -opracowanie piśmiennictwa, G -pozyskanie funduszy Wstęp. Brak skutecznych rozwiązań systemowych w zakresie opieki podstawowej i długi czas oczekiwania na konsultację w ramach ambulatoryjnej opieki specjalistycznej są przyczyną zgłoszeń do SOR pacjentów nie wymagających zastosowania procedur ratowniczych. Możliwość szybkiego dotarcia do SOR oraz nieograniczony dostęp pacjent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It can therefore be assumed that at least some of these hospitalizations could have been caused by the need for longer observation and in-depth diagnostics in order to establish a more precise diagnosis, rather than the urgency of admission to the ward. Nonetheless, in the study material, the percentage of hospitalizations was quite high at 22%, higher than the 10%-14% reported in the United States [20], Portugal, Slovenia [21], or some Polish centers [22]. Generally, research into factors associated with non-specific ED diagnoses is scarce, even though they may encompass from 15% [23] to 37% [24] of all ED visits.…”
Section: Discussionmentioning
confidence: 68%
“…It can therefore be assumed that at least some of these hospitalizations could have been caused by the need for longer observation and in-depth diagnostics in order to establish a more precise diagnosis, rather than the urgency of admission to the ward. Nonetheless, in the study material, the percentage of hospitalizations was quite high at 22%, higher than the 10%-14% reported in the United States [20], Portugal, Slovenia [21], or some Polish centers [22]. Generally, research into factors associated with non-specific ED diagnoses is scarce, even though they may encompass from 15% [23] to 37% [24] of all ED visits.…”
Section: Discussionmentioning
confidence: 68%
“…It can therefore be assumed that at least some of these hospitalizations could have been caused by the need for longer observation and in-depth diagnostics in order to establish a more precise diagnosis, rather than the urgency of admission to the ward. In the study data, the percentage of hospitalizations was 22%-higher than the 10-14% reported in the United States [20], Portugal and Slovenia [21], or some Polish centres [22]. On the other hand, in Australia, 28% of all presentations to the ED in 2021-2022 ended in hospital admission, and this proportion varied across states and territories from 23% to 34% [23].…”
Section: Discussionmentioning
confidence: 89%